"Mrs. Nixon's Goodwill Mission": The Great Peruvian Earthquake, Rhetorical History, and the Art of Personal Diplomacy. Issue 2 (22nd February 2022) - Lehn, Melody
Abstract : Though widely perceived as an ineffectual first lady, Pat Nixon was a diplomatic asset to the Nixon administration. This rhetorical history investigates her inventive use of "personal diplomacy" on a goodwill mission to Peru in 1970. Despite competing directives from the West Wing and State Department, Nixon elected to speak in her own voice and deployed personal diplomacy as a multifaceted rhetorical strategy to accomplish humanitarian goals. Nixon's rhetorical performance yielded significant, yet limited diplomatic gains and complicates recent scholarship suggesting that the gendered nature of first lady diplomacy renders it a largely routine, essentially symbolic, and politically safe endeavor .